Eugenol ameliorates uveitis in mice with experimental autoimmune encephalomyelitis through the suppression of key inflammatory genes - Sungmoo Hong; Kyungsook Jung; Meejung Ahn; Jeongtae Kim; Changjong Moon; Taekyun Shin (Animal Cells and Systems, 2024)
Visual impairment associated with uveitis is among the potential complications in multiple sclerosis (MS) and its animal model, experimental autoimmune encephalomyelitis (EAE). Bioinformatics analyses have shown that some hub genes are closely associated with the molecular mechanisms underlying uveitis in EAE. This study evaluated whether 4-allyl-2-methoxyphenol (eugenol) can mitigate the pathogenesis of uveitis in EAE through the interruption of key uveitogenic gene expression. Myelin oligodendrocyte glycoprotein35–55 (MOG) peptide-immunized C57BL/6 mice were injected intraperitoneally with eugenol. The eyeballs and spinal cords of EAE mice with or without eugenol treatment were collected simultaneously and immunohistochemical and molecular biological analyses were conducted. Eugenol treatment significantly ameliorated hindlimb paralysis. Ionized calcium-binding adapter molecule 1 (Iba-1) immunohistochemistry showed that the inflammatory response was significantly reduced in the uvea of eugenol-treated EAE mice compared with vehicle-treated controls. Eugenol also significantly reduced the expression of key uveitogenic genes including C1qb and Tyrobp. The suppressive effect of eugenol on inflammation was also observed in the spinal cord, as determined by the suppression of Iba-1-positive microglial cells. Together, these results suggest that the ameliorative effect of eugenol against EAE uveitis is associated with the suppression of key proinflammatory genes, which may represent targets for the treatment of uveitis.